STRATEGI KOMUNIKASI ANTAR BUDAYA DALAM MENGHADAPI KEBERAGAMAN SOSIAL DAN DINAMIKA GLOBAL (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Cultural diversity is a social reality that is inseparable from the life of modern society, particularly in the era of globalization characterized by the increasing intensity of interactions among individuals and groups from diverse cultural backgrounds. Differences in values, norms, language, and communication patterns often lead to misunderstandings that may trigger social conflicts or create barriers in organizational interactions. This article aims to examine intercultural communication strategies in addressing social diversity and global dynamics by integrating anthropological, social, and organizational perspectives. The methodemployed is a literature review, analyzing three scholarly journals and three reference books that discuss cross-cultural communication. The findings indicate that effective intercultural communication requires an understanding of cultural contexts, the ability to adapt messages, and the sensitive management of verbal and nonverbal communication. Prominent strategies include the development of intercultural competence, the role of mediators or neutral parties, the utilization of intercultural forums, and the application of communication principles oriented toward mutual understanding and respect for differences. In addition to fostering social harmony and peace, intercultural communication also contributes to enhancingthe effectiveness of interactions within organizational and business environments. Therefore, intercultural communication is a strategic skill that needs to be continuously developed to address the complexity of social diversity in a global context.